Mathematical Problem-Solving Ability of Class X Students SMAN 5 Serang City in Completing Story Problems - Hamidah Hamidah; Vivi Alfiah; Ine Safiyanah; Jaka Wijaya Kusuma; Lia Riani; Uswatun Hasanah (Universitas Muhammadiyah Enrekang, 2023)
Problem-solving ability is one of the goals of learning mathematics and is demonstrated by the ability to understand the problems that occur, compile a settlement plan, carry out the plan, and review the solutions that have been obtained. This research aims to discover and describe students' mathematical problem-solving abilities in the sub-material Comparison of Trigonometry in Right-Angled Triangles. This type of research is qualitative and uses descriptive methods. The sample used in the study was 46 students from class X MIPA 1. The data collection technique used a problem-solving ability test in the form of two-story questions. The results obtained from this study are the average percentage of achievement indicators of students' mathematical problem-solving abilities. The indicator of understanding the problem is 77.55%, the indicator of compiling a settlement plan is 88.75%, the indicator of carrying out the plan is 96.05%, and the indicator of reviewing is 63.4%. It can be concluded that class X students at SMAN 5 Serang City have high mathematical problem-solving abilities